Combined RNA-seq and Phenotype Analysis Reveals a Potential Molecular Mechanism of the Difference in Grain Size of Naked Barley From the Qinghai–Tibetan Plateau - Kong, Doudou; Xu, Jinqing; Wang, Lei; Wang, Handong; You, En; Li, Xiaolan; Chen, Tongrui; Shen, Yuhu (Frontiers in Plant Science, 2022)
To understand the molecular mechanism controlling the size of barley grains, a number of traits were analysed and RNA-seq was conducted on grains of two barley materials with a significant difference in 1000-grain weight after flowering. The trait dataset delineates the dynamic changes in grain size after flowering, and it provides an understanding of the source of the difference in 1000-grain weight. By comparing the transcripts of barley grains at several stages after flowering, we identified the gene expression characteristics and significantly enriched pathways in each stage. At the early stage of grain development, genes involved in fatty acid metabolism, plant hormone signal transduction and pathways involved in cytoskeleton formation were significantly upregulated. At the later stage of grain development, genes involved in starch synthesis, glucose metabolism and other pathways were significantly upregulated. Further, we used weighted gene coexpression network analysis (WGCNA) and correlation analysis of trait datasets to identify the coexpressed gene modules significantly associated with traits such as grain length, grain width and dry weight. After comparing the modules with the differentially expressed gene set, 12 candidate genes were selected, and among these, 4 genes were homologous to genes that regulate grain size in rice and other plants. The combined analysis identified many potential key regulatory factors that may control barley grain size and yield potential, thus providing new insights into the molecular mechanism of barley grain size.